Preparation method of positive electrode material, pole piece and battery
Through the pure dry process and the use of fluorine replenishing agent, the problem of F element loss of sodium vanadium fluorine phosphate positive electrode material was solved, and a high-purity and good conductivity carbon-coated sodium vanadium fluorine phosphate positive electrode material was prepared, realizing the possibility of large-scale production.
Patent Information
- Application Number
- CN202510087199.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The synthesis of existing sodium vanadium fluorophosphate positive electrode materials is prone to loss of F element, resulting in component deviation, insufficient purity, poor product consistency, low specific capacity, and difficult to achieve large-scale production.
The carbon-coated sodium vanadium fluorine phosphate positive electrode material is prepared by using a pure dry process, through the steps of pre-dispersion and mixing of high-speed disperser, ball milling and refining, high-speed shear dispersion and roll granulation, and the F-loss supplementation is used to improve the conductivity and specific capacity of the material through step-by-step sintering.
The preparation of carbon-coated sodium vanadium fluorophosphate positive electrode material with good purity and uniformity is achieved, which improves the conductivity and specific capacity of the material, simplifies the process, reduces energy consumption and wastewater treatment, and is suitable for large-scale production.
Smart Images

Figure CN119864403A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium battery preparation, and specifically relates to a positive electrode material preparation method, a pole piece, and a battery. Background Art
[0002] Sodium vanadium fluorophosphate (Na3V2(PO4)2F3) is an important positive electrode material for sodium ion batteries. It has high specific capacity and high energy density and is considered to be one of the most promising high-voltage sodium ion battery positive electrode materials. This material can provide a high energy storage capacity and help improve the overall performance of sodium ion batteries. However, the synthesis of this material is prone to the loss of F elements, which makes the material composition deviation, insufficient purity, poor product consistency, low specific capacity, and difficult to mass produce.
[0003] There are two existing methods for synthesizing sodium vanadium fluorophosphate: the first is a pure liquid phase high temperature and high pressure hydrothermal method: using water-soluble raw materials, dissolving and dispersing them in a high temperature and high pressure hydrothermal reactor for reaction synthesis, generally requiring secondary sintering carbon coating to improve conductivity, and obtaining a positive electrode material with high purity, good consistency and high specific capacity; however, due to the complex process, it is not conducive to continuous large-scale production; the second is a liquid phase mixing + solid phase sintering process: dissolving and dispersing sodium source / fluorine source, vanadium source, phosphorus source, carbon source (citric acid), pH regulator (ammonia water), spray drying to obtain a precursor powder, and then solid phase sintering to obtain a positive electrode material. Because this process is relatively simple, it can be continuously mass-produced and can be carbon-coated once; the pH is adjusted by ammonia water, combined with segmented sintering to reduce the loss of F elements, and a large amount of ammonia nitrogen gas is generated at the same time, which puts a lot of pressure on environmental protection treatment; the precursor is obtained by liquid phase mixing combined with spray drying. Since a large amount of gas will be generated during the process, the uniformity and density of the obtained precursor are poor, resulting in low powder compaction density and low loading capacity, thus affecting production capacity.
[0004] Therefore, it is necessary to design a method for preparing a positive electrode material that improves the above problems. Summary of the invention
[0005] In order to solve the problems of the prior art, the present invention provides a method for preparing a positive electrode material, the preparation method comprising the following steps:
[0006] Step 1, putting the sodium vanadium fluorophosphate raw material, the carbon source and the fluorine replenishing agent into a high-speed disperser for pre-dispersion and mixing to obtain a pre-mixed raw material;
[0007] Step 2, grinding the premixed raw materials by a ball mill;
[0008] Step 3, sending the ball-milled raw materials into a high-speed disperser for high-speed shearing and dispersion until a bonding raw material is formed;
[0009] Step 4, rolling and granulating the bonded body raw material through a roller granulator to obtain a sodium vanadium fluorophosphate precursor;
[0010] Step 5: sinter the sodium vanadium fluorophosphate precursor once to obtain a carbon-coated sodium vanadium fluorophosphate positive electrode material.
[0011] In some optional embodiments, in step 1, the sodium vanadium fluorophosphate raw material includes a sodium source / fluorine source, a phosphorus source and a vanadium source;
[0012] The sodium source / fluorine source is sodium fluoride, the phosphorus source is ammonium dihydrogen phosphate or phosphoric acid, and the vanadium source is vanadium pentoxide or ammonium metavanadate; wherein the molar ratio of the sodium source / fluorine source, the phosphorus source and the vanadium source is 3:2:2;
[0013] The carbon source is glucose or citric acid, and the mass of the carbon source is 1-10wt% of the total mass of the sodium vanadium fluorophosphate raw material;
[0014] The fluorine replenisher is used to replenish fluorine loss to ensure the completion and phase purity of the synthesized sodium vanadium fluorophosphate components; the fluorine replenisher also acts as a binder to bond the particles during high-speed shear dispersion, and after roller granulation, the density of the sodium vanadium fluorophosphate precursor is higher; wherein the fluorine replenisher is polyvinylidene fluoride or polytetrafluoroethylene; the fluorine replenisher is polyvinylidene fluoride or polytetrafluoroethylene, and the mass of the fluorine replenisher is 1-8wt% of the total mass of the sodium vanadium fluorophosphate raw material.
[0015] In some optional embodiments, in step 2, the median particle size D50 of the raw material particles after ball milling is ≤6 microns.
[0016] In some optional embodiments, in step 3, when the high-speed disperser performs high-speed shear dispersion, the rotation speed of the high-speed disperser is 800-1800 rpm.
[0017] In some optional embodiments, in step 4, the roller pressing pressure of the roller granulator for roller granulation is ≥7 MPa.
[0018] In some optional embodiments, in step 5, the primary sintering is step-by-step sintering, specifically:
[0019] After the sodium vanadium fluorophosphate precursor is subjected to a first sintering reaction at a first sintering temperature, the temperature is raised to a second sintering temperature for a second sintering reaction;
[0020] Wherein, the conditions of the first sintering reaction are:
[0021] The first sintering temperature is 300-400°C, and the first sintering reaction time is 5-10h;
[0022] The conditions of the second sintering reaction are:
[0023] The second sintering temperature is 500-750°C, and the second sintering reaction time is 8-12h.
[0024] The second aspect of the present invention provides a carbon-coated sodium vanadium fluorophosphate positive electrode material prepared by the above preparation method;
[0025] A third aspect of the present invention provides a pole piece, comprising the carbon-coated sodium vanadium fluorophosphate positive electrode material prepared by the above-mentioned preparation method.
[0026] A fourth aspect of the present invention provides a battery, comprising the carbon-coated sodium vanadium fluorophosphate positive electrode material prepared by the preparation method described above or the electrode sheet described above;
[0027] Beneficial effects of the present invention:
[0028] (1) The present invention uses a pure dry process, which is simpler than the hydrothermal process and can be continuously mass-produced. In addition, the pure dry process used in the present invention has less wastewater treatment in terms of environmental protection compared to the liquid phase + solid phase sintering process, and does not require a spray drying process, so the energy consumption is lower;
[0029] (2) The process of the present invention is set up. Since there are many kinds of raw materials for preparing positive electrode materials, and the particle sizes of various raw materials are different, the raw materials are first pre-mixed by high-speed dispersion, and then the pre-mixed raw materials are refined by ball milling. Finally, they are dispersed at high speed to ensure that the raw materials are evenly dispersed. The fluorine replenisher also serves as a binder. The fiberization of the binder is achieved by high-speed shear force, and different particles in the raw materials after ball milling are bonded. The bonded raw materials are rolled and granulated by a roller granulator, and finally a sodium vanadium fluorophosphate precursor with higher density is obtained. Therefore, the unit volume loading is higher in large-scale production, which is conducive to improving production capacity. The carbon-coated sodium vanadium fluorophosphate positive electrode material is obtained after one-time sintering, which has good conductivity and high specific capacity, and can be continuously produced on a large scale.
[0030] (3) The preparation method of the positive electrode material of the present application uses low-cost carbon sources such as glucose and citric acid as raw materials, thereby reducing the production cost of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of the carbon-coated sodium vanadium fluorophosphate positive electrode material prepared in Example 1 of the present invention;
[0032] Figure 2 This is the XRD pattern of the carbon-coated sodium vanadium fluorophosphate prepared in Example 1 of the present invention;
[0033] Figure 3 This is a schematic diagram of the charge and discharge curve of a battery made from the carbon-coated sodium vanadium fluorophosphate positive electrode material of Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] A first aspect of the present invention provides a method for preparing a positive electrode material, the method comprising the following steps:
[0036] Step 1, putting the sodium vanadium fluorophosphate raw material, the carbon source and the fluorine replenishing agent into a high-speed disperser for pre-dispersion and mixing to obtain a pre-mixed raw material;
[0037] Step 2, grinding the premixed raw materials by a ball mill;
[0038] Step 3, sending the ball-milled raw materials into a high-speed disperser for high-speed shearing and dispersion until a bonding raw material is formed;
[0039] Step 4, rolling and granulating the bonded body raw material through a roller granulator to obtain a sodium vanadium fluorophosphate precursor;
[0040] Step 5: sinter the sodium vanadium fluorophosphate precursor once to obtain a carbon-coated sodium vanadium fluorophosphate positive electrode material.
[0041] In some optional embodiments, in step 1, the sodium vanadium fluorophosphate raw material includes a sodium source / fluorine source, a phosphorus source and a vanadium source;
[0042] The sodium source / fluorine source is sodium fluoride, the phosphorus source is ammonium dihydrogen phosphate or phosphoric acid, and the vanadium source is vanadium pentoxide or ammonium metavanadate; wherein the molar ratio of the sodium source / fluorine source, the phosphorus source and the vanadium source is 3:2:2;
[0043] The carbon source is glucose or citric acid, and the mass of the carbon source is 1-10wt% of the total mass of the sodium vanadium fluorophosphate raw material;
[0044] The fluorine replenisher is used to replenish fluorine loss to ensure the completion and phase purity of the synthesized sodium vanadium fluorophosphate components; the fluorine replenisher also acts as a binder to bond the particles during high-speed shear dispersion, and after roller granulation, the sodium vanadium fluorophosphate precursor has a higher density; wherein the fluorine replenisher is polyvinylidene fluoride or polytetrafluoroethylene, and the mass of the fluorine replenisher is 1-8wt% of the total mass of the sodium vanadium fluorophosphate raw material.
[0045] In some optional embodiments, in step 2, the median particle size D50 of the raw material particles after ball milling is ≤6 microns.
[0046] In some optional embodiments, in step 3, when the high-speed disperser performs high-speed shear dispersion, the rotation speed of the high-speed disperser is 800-1800 rpm.
[0047] In some optional embodiments, in step 4, the roller pressing pressure of the roller granulator for roller granulation is ≥7 MPa.
[0048] In some optional embodiments, in step 5, the primary sintering is step-by-step sintering, specifically:
[0049] After the sodium vanadium fluorophosphate precursor is subjected to a first sintering reaction at a first sintering temperature, the temperature is raised to a second sintering temperature for a second sintering reaction;
[0050] Wherein, the conditions of the first sintering reaction are:
[0051] The first sintering temperature is 300-400°C, and the first sintering reaction time is 5-10h;
[0052] The conditions of the second sintering reaction are:
[0053] The second sintering temperature is 500-750°C, and the second sintering reaction time is 8-12h.
[0054] The second aspect of the present invention provides a carbon-coated sodium vanadium fluorophosphate positive electrode material prepared by the above preparation method;
[0055] A third aspect of the present invention provides a pole piece, comprising the carbon-coated sodium vanadium fluorophosphate positive electrode material prepared by the above-mentioned preparation method.
[0056] A fourth aspect of the present invention provides a battery, comprising the carbon-coated sodium vanadium fluorophosphate positive electrode material prepared by the preparation method described above or the electrode sheet described above;
[0057] Example 1. This example provides a method for preparing a positive electrode material, comprising the following steps: (1) placing a sodium vanadium fluorophosphate raw material, a carbon source and a fluorine replenisher into a high-speed disperser for pre-dispersion and mixing to obtain a pre-mixed raw material; wherein the sodium source / fluorine source is sodium fluoride, the phosphorus source is ammonium dihydrogen phosphate, the vanadium source is vanadium pentoxide, and the molar ratio of the sodium source / fluorine source, the phosphorus source and the vanadium source is 3:2:2;
[0058] The carbon source is glucose, the mass of the carbon source is 4wt% of the total mass of the sodium vanadium fluorophosphate raw material, the mass of the fluorine supplement is 2wt% of the total mass of the sodium vanadium fluorophosphate raw material, and the mixture is weighed according to the actual weight, wherein sodium fluoride is 304.561g, vanadium pentoxide is 439.736g, sodium dihydrogen phosphate is 834.332g, glucose is 63.145g, and polytetrafluoroethylene is 31.573g; (2) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 4.8 microns; (3) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 4.8 microns; The raw materials after curing are sent to a high-speed disperser for high-speed shear dispersion until a bonding body raw material is formed; wherein the speed of the high-speed disperser is 1200rpm; (4) the bonding body raw material is rolled and granulated by a roller granulator to obtain a sodium vanadium fluorophosphate precursor; wherein the roller pressure of the roller granulator for rolling and granulating is 7MPa; (5) the sodium vanadium fluorophosphate precursor is sintered once, and the once sintering is step-by-step sintering, the room temperature is heated to 350°C and kept warm for 8 hours, and then heated to 720°C and kept warm for 10 hours to obtain a carbon-coated sodium vanadium fluorophosphate positive electrode material;
[0059] Example 2. This example provides a method for preparing a positive electrode material, comprising the following steps: (1) placing a sodium vanadium fluorophosphate raw material, a carbon source and a fluorine replenisher into a high-speed disperser for pre-dispersion and mixing to obtain a pre-mixed raw material; wherein the sodium source / fluorine source is sodium fluoride, the phosphorus source is ammonium dihydrogen phosphate, the vanadium source is vanadium pentoxide, and the molar ratio of the sodium source / fluorine source, the phosphorus source and the vanadium source is 3:2:2;
[0060] The carbon source is glucose, the mass of the carbon source is 4wt% of the total mass of the sodium vanadium fluorophosphate raw material, the mass of the fluorine supplement is 3wt% of the total mass of the sodium vanadium fluorophosphate raw material, and the mixture is weighed according to the actual weight, wherein sodium fluoride is 304.561g, vanadium pentoxide is 439.736g, ammonium dihydrogen phosphate is 834.332g, glucose is 63.145g, and polyvinylidene fluoride is 47.359g; (2) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 5.0 microns; (3) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 5.0 microns; The raw materials after curing are sent to a high-speed disperser for high-speed shear dispersion until a bonding body raw material is formed; wherein the speed of the high-speed disperser is 1200rpm; (4) the bonding body raw material is rolled and granulated by a roller granulator to obtain a sodium vanadium fluorophosphate precursor; wherein the roller pressure of the roller granulator for rolling and granulating is 7MPa; (5) the sodium vanadium fluorophosphate precursor is sintered once, and the once sintering is step-by-step sintering, the room temperature is heated to 350°C and kept warm for 8 hours, and then heated to 720°C and kept warm for 10 hours to obtain a carbon-coated sodium vanadium fluorophosphate positive electrode material;
[0061] Embodiment 3. This embodiment provides a method for preparing a positive electrode material, comprising the following steps: (1) placing a sodium vanadium fluorophosphate raw material, a carbon source and a fluorine replenishing agent into a high-speed disperser for pre-dispersion and mixing to obtain a pre-mixed raw material; wherein the sodium source / fluorine source is sodium fluoride, the phosphorus source is ammonium dihydrogen phosphate, the vanadium source is vanadium pentoxide, and the molar ratio of the sodium source / fluorine source, the phosphorus source and the vanadium source is 3:2:2;
[0062] The carbon source is citric acid, the mass of the carbon source is 3.5wt% of the total mass of the sodium vanadium fluorophosphate raw material, the mass of the fluorine replenisher is 1.5wt% of the total mass of the sodium vanadium fluorophosphate raw material, and the mixture is weighed according to the actual weight, wherein sodium fluoride is 304.561g, vanadium pentoxide is 439.736g, ammonium dihydrogen phosphate is 834.332g, citric acid is 55.252g, and polytetrafluoroethylene is 23.679g; (2) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 4.8 microns; (3) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 4.8 microns; The refined raw material is sent to a high-speed disperser for high-speed shear dispersion until a bonding body raw material is formed; wherein the speed of the high-speed disperser is 1400rpm; (4) the bonding body raw material is roller-granulated by a roller granulator to obtain a sodium vanadium fluorophosphate precursor; wherein the roller pressure of the roller granulator for roller granulation is 7MPa; (5) the sodium vanadium fluorophosphate precursor is sintered once, the once sintering is step-by-step sintering, the room temperature is heated to 350°C and kept warm for 8 hours, and then heated to 720°C and kept warm for 10 hours to obtain a carbon-coated sodium vanadium fluorophosphate positive electrode material;
[0063] Example 4. This example provides a method for preparing a positive electrode material, comprising the following steps: (1) placing a sodium vanadium fluorophosphate raw material, a carbon source and a fluorine replenisher into a high-speed disperser for pre-dispersion and mixing to obtain a pre-mixed raw material; wherein the sodium source / fluorine source is sodium fluoride, the phosphorus source is ammonium dihydrogen phosphate, the vanadium source is ammonium metavanadate, and the molar ratio of the sodium source / fluorine source, the phosphorus source and the vanadium source is 3:2:2;
[0064] The carbon source is citric acid, the mass of the carbon source is 3.5wt% of the total mass of the sodium vanadium fluorophosphate raw material, the mass of the fluorine replenisher is 1.5wt% of the total mass of the sodium vanadium fluorophosphate raw material, and the mixture is weighed according to the actual weight, wherein sodium fluoride is 304.561g, ammonium metavanadate is 565.651g, ammonium dihydrogen phosphate is 834.332g, citric acid is 55.252g, and polytetrafluoroethylene is 23.679g; (2) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 4.8 microns; (3) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 4.8 microns; The refined raw material is sent to a high-speed disperser for high-speed shear dispersion until a bonding body raw material is formed; wherein the speed of the high-speed disperser is 1400rpm; (4) the bonding body raw material is roller-granulated by a roller granulator to obtain a sodium vanadium fluorophosphate precursor; wherein the roller pressure of the roller granulator for roller granulation is 7MPa; (5) the sodium vanadium fluorophosphate precursor is sintered once, the once sintering is step-by-step sintering, the room temperature is heated to 350°C and kept warm for 8 hours, and then heated to 720°C and kept warm for 10 hours to obtain a carbon-coated sodium vanadium fluorophosphate positive electrode material;
[0065] Example 5. This example provides a method for preparing a positive electrode material, comprising the following steps: (1) placing a sodium vanadium fluorophosphate raw material, a carbon source and a fluorine replenisher into a high-speed disperser for pre-dispersion and mixing to obtain a pre-mixed raw material; wherein the sodium source / fluorine source is sodium fluoride, the phosphorus source is phosphoric acid, the vanadium source is vanadium pentoxide, and the molar ratio of the sodium source / fluorine source, the phosphorus source and the vanadium source is 3:2:2;
[0066] The carbon source is citric acid, the mass of the carbon source is 3.5wt% of the total mass of the sodium vanadium fluorophosphate raw material, the mass of the fluorine replenisher is 1.5wt% of the total mass of the sodium vanadium fluorophosphate raw material, and the mixture is weighed according to the actual weight, wherein sodium fluoride is 304.561g, vanadium pentoxide is 439.736g, phosphoric acid is 827.843g, citric acid is 55.252g, and polytetrafluoroethylene is 23.679g; (2) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 4.8 microns; (3) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 4.8 microns; The raw materials after curing are sent to a high-speed disperser for high-speed shear dispersion until a bonding body raw material is formed; wherein the speed of the high-speed disperser is 1400rpm; (4) the bonding body raw material is rolled and granulated by a roller granulator to obtain a sodium vanadium fluorophosphate precursor; wherein the roller pressure of the roller granulator for rolling and granulating is 7MPa; (5) the sodium vanadium fluorophosphate precursor is sintered once, and the once sintering is step-by-step sintering, the room temperature is heated to 350°C and kept warm for 8 hours, and then heated to 720°C and kept warm for 10 hours to obtain a carbon-coated sodium vanadium fluorophosphate positive electrode material;
[0067] Example 6. This example provides a method for preparing a positive electrode material, comprising the following steps: (1) placing a sodium vanadium fluorophosphate raw material, a carbon source and a fluorine replenisher into a high-speed disperser for pre-dispersion and mixing to obtain a pre-mixed raw material; wherein the sodium source / fluorine source is sodium fluoride, the phosphorus source is ammonium dihydrogen phosphate, the vanadium source is vanadium pentoxide, and the molar ratio of the sodium source / fluorine source, the phosphorus source and the vanadium source is 3:2:2;
[0068] The carbon source is citric acid, the mass of the carbon source is 3.5wt% of the total mass of the sodium vanadium fluorophosphate raw material, the mass of the fluorine replenisher is 1.5wt% of the total mass of the sodium vanadium fluorophosphate raw material, and the mixture is weighed according to the actual weight, wherein sodium fluoride is 304.561g, vanadium pentoxide is 439.736g, ammonium dihydrogen phosphate is 834.332g, citric acid is 55.252g, and polytetrafluoroethylene is 23.679g; (2) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 4.8 microns; (3) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 4.8 microns; The refined raw material is sent to a high-speed disperser for high-speed shear dispersion until a bonding body raw material is formed; wherein the speed of the high-speed disperser is 1400rpm; (4) the bonding body raw material is roller-granulated by a roller granulator to obtain a sodium vanadium fluorophosphate precursor; wherein the roller pressure of the roller granulator for roller granulation is 9MPa; (5) the sodium vanadium fluorophosphate precursor is sintered once, the once sintering is step-by-step sintering, the room temperature is heated to 350°C and kept warm for 8 hours, and then heated to 720°C and kept warm for 10 hours to obtain a carbon-coated sodium vanadium fluorophosphate positive electrode material;
[0069] Comparative Example 1, (1) putting sodium vanadium fluorophosphate raw material, carbon source and fluorine replenishing agent into a high-speed disperser for pre-dispersion and mixing to obtain a pre-mixed raw material; wherein the sodium source / fluorine source is sodium fluoride, the phosphorus source is ammonium dihydrogen phosphate, the vanadium source is vanadium pentoxide, and the molar ratio of the sodium source / fluorine source, the phosphorus source and the vanadium source is 3:2:2;
[0070] The carbon source is citric acid, the mass of the carbon source is 3.5wt% of the total mass of the sodium vanadium fluorophosphate raw material, the mass of the fluorine replenisher is 1.5wt% of the total mass of the sodium vanadium fluorophosphate raw material, and the mixture is weighed according to the actual weight, wherein sodium fluoride is 304.561g, vanadium pentoxide is 439.736g, ammonium dihydrogen phosphate is 834.332g, citric acid is 55.252g, and polyvinylidene fluoride is 23.679g; (2) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 4.9 microns; (3) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 4.9 microns; The ground raw material is sent to a high-speed disperser for high-speed shear dispersion until a bonding body raw material is formed; wherein the speed of the high-speed disperser is 500 rpm; (4) the bonding body raw material is rolled and granulated by a roller granulator to obtain a sodium vanadium fluorophosphate precursor; wherein the roller pressure of the roller granulator for rolling and granulating is 7 MPa; (5) the sodium vanadium fluorophosphate precursor is sintered once, and the once sintering is step-by-step sintering, the room temperature is heated to 350° C. and kept warm for 8 hours, and then heated to 720° C. and kept warm for 10 hours, to obtain a carbon-coated sodium vanadium fluorophosphate positive electrode material;
[0071] Comparative Example 2, (1) putting sodium vanadium fluorophosphate raw material, carbon source and fluorine replenishing agent into a high-speed disperser for pre-dispersion and mixing to obtain a premixed raw material; wherein the sodium source / fluorine source is sodium fluoride, the phosphorus source is ammonium dihydrogen phosphate, the vanadium source is vanadium pentoxide, and the molar ratio of the sodium source / fluorine source, the phosphorus source and the vanadium source is 3:2:2;
[0072] The carbon source is glucose, and the mass of the carbon source is 4wt% of the total mass of the sodium vanadium fluorophosphate raw material. The mixture is weighed according to the actual weight, wherein sodium fluoride is 304.561g, vanadium pentoxide is 439.736g, ammonium dihydrogen phosphate is 834.332g, glucose is 63.145g, and polyvinylidene fluoride is 23.679g; (2) the premixed raw materials are ball-milled by a ball mill; the median particle size D50 of the raw material particles after ball milling is 4.8 microns; (3) the ball-milled raw materials are fed into a high-speed disperser (4) the raw material of the binder is subjected to roller granulation by a roller granulator to obtain a sodium vanadium fluorophosphate precursor; wherein the roller pressure of the roller granulator for roller granulation is 7 MPa; (5) the sodium vanadium fluorophosphate precursor is subjected to a first sintering, wherein the first sintering is a step-by-step sintering, the room temperature is raised to 350° C. and kept warm for 8 hours, and then the temperature is raised to 720° C. and kept warm for 10 hours, to obtain a carbon-coated sodium vanadium fluorophosphate positive electrode material;
[0073] Comparative Example 3, (1) putting sodium vanadium fluorophosphate raw material, carbon source and fluorine replenishing agent into a high-speed disperser for pre-dispersion and mixing to obtain a pre-mixed raw material; wherein the sodium source / fluorine source is sodium fluoride, the phosphorus source is ammonium dihydrogen phosphate or phosphoric acid, the vanadium source is vanadium pentoxide, and the molar ratio of the sodium source / fluorine source, the phosphorus source and the vanadium source is 3:2:2;
[0074] The carbon source is citric acid, the mass of the carbon source is 3.5wt% of the total mass of the sodium vanadium fluorophosphate raw material, the mass of the fluorine replenisher is 1.5wt% of the total mass of the sodium vanadium fluorophosphate raw material, and the mixture is weighed according to the actual weight, wherein sodium fluoride is 304.561g, vanadium pentoxide is 439.736g, ammonium dihydrogen phosphate is 834.332g, citric acid is 55.252g, and polyvinylidene fluoride is 23.679g; (2) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 4.9 microns; (3) the premixed raw materials are ball-milled; the median particle size D50 of the raw material particles after ball milling is 4.9 microns; The ground raw material is sent to a high-speed disperser for high-speed shear dispersion until a bonding body raw material is formed; wherein the speed of the high-speed disperser is 1200rpm; (4) the bonding body raw material is roller-pressed and granulated by a roller granulator to obtain a sodium vanadium fluorophosphate precursor; wherein the roller pressure of the roller granulator for roller granulation is 5MPa; (5) the sodium vanadium fluorophosphate precursor is sintered once, and the once sintering is step-by-step sintering, the room temperature is heated to 350°C and kept warm for 8 hours, and then heated to 720°C and kept warm for 10 hours, to obtain a carbon-coated sodium vanadium fluorophosphate positive electrode material;
[0075] Performance testing: testing the performance of the materials provided in the embodiments and comparative examples;
[0076] (I) Detection method: 1. Scanning electron microscopy: The materials provided in the embodiments and comparative examples were subjected to scanning electron microscopy to observe the material morphology.
[0077] 2. XRD test: Use a powder X-ray diffractometer to perform powder testing in the diffraction angle range of 10-80° 2θ.
[0078] 3. Button cell production: The positive electrode material, adhesive PVDF and conductive carbon black (Super P) are mixed in a ratio of 94:3:3 and dissolved in the solvent NMP. After sufficient stirring and degassing, the slurry is filtered to obtain a slurry. The obtained slurry is coated on the surface of the current collector aluminum foil using an automatic coating machine. The coated electrode is dried at 105°C for more than 12 hours under blast and vacuum conditions, and the positive electrode is obtained after roller pressing. The positive electrode is punched into a disc with a diameter of 12mm, the negative electrode is a metal sodium sheet, the glass fiber membrane is used as a diaphragm, and the electrolyte is 1mol / L NaPF6 dissolved in an organic solution of EC:DEC=1:1. The CR2032 button cell is assembled in an argon protection glove box with a water and oxygen content of less than 1ppm. The battery charge and discharge current of 1C is 120mA / g, and the cycle curve is detected in the voltage range of 2.5-4.3V.
[0079] 4. Powder bulk density test: Weigh a certain amount of precursor powder and naturally feed it into a square sagger of a certain size and volume through a loader, and gently press and flatten it with a scraper. Weigh the mass of the empty sagger and the sagger filled with material respectively, and divide it by the volume of the sagger to get the powder bulk density.
[0080] 5. Powder compaction density test: Weigh a certain amount of powder sample and put it into a cylindrical mold. Apply pressure to compress the powder into a disc shape. After maintaining the pressure at 3T for a certain period of time, read the volume of the compressed material and obtain the powder compaction density through the mass-to-volume ratio.
[0081] (II) Test results. The performance test data of the positive electrode materials prepared in the embodiments and comparative examples are shown in Table 1 below;
[0082] Table 1
[0083]
[0084] Based on the performance test data of the positive electrode materials obtained in the above embodiments and comparative examples, it can be known that: (1) the positive electrode materials obtained in each embodiment of the present invention have a high loose density of the sodium vanadium fluorophosphate precursor, and the prepared positive electrode material has a high powder compaction density, good conductivity, and high specific capacity. In comparative example 1, when preparing the positive electrode material, the speed of the high-speed disperser is 500 rpm, so that the fluorine replenishing agent has no bonding performance, and the obtained precursor has a low loose density; in comparative example 2, when preparing the positive electrode material, no fluorine replenishing agent is added to the sodium vanadium fluorophosphate raw material, and the obtained positive electrode material has many impurities, low purity, low precursor loose density, low specific capacity, and low loading capacity, which affects the improvement of production capacity; (2) Figure 1 is a scanning electron microscope image of the carbon-coated sodium vanadium fluorophosphate positive electrode material prepared in Example 1. Figure 1 It can be seen that the prepared carbon-coated sodium vanadium fluorophosphate cathode material is uniform nanoparticles, indicating that the sodium source / fluorine source, phosphorus source, vanadium source, carbon source and fluorine replenisher are in sufficient contact and react with each other; Figure 2 is the XRD pattern of the carbon-coated sodium vanadium fluorophosphate prepared in Example 1, Figure 2 The provided XRD diffraction pattern shows that the XRD diffraction spectrum of the prepared carbon-coated sodium vanadium fluorophosphate is completely consistent with the standard diffraction spectrum, indicating that the preparation method of the present invention adds a fluorine replenishing agent, and the fluorine replenishing agent replenishes the F loss, so that the preparation process of the carbon-coated sodium vanadium fluorophosphate obtains pure phase sodium vanadium fluorophosphate; Figure 3 is the charge and discharge curve of the battery made from the positive electrode material of Example 1. Figure 3 It can be seen that the battery voltage made from the positive electrode material of Example 1 is 4.2V, and the constant current charging is performed with a charging current of 1C and a discharge capacity of 118.5mAh / g; the carbon-coated sodium vanadium fluorophosphate positive electrode material obtained by the preparation method has a higher specific capacity, and the battery made from the positive electrode material has a long cycle life;
[0085] It should be noted that: (1) The present invention uses a pure dry process, which is simpler than the hydrothermal process and can be produced on a large scale continuously, with the focus on the amount of wastewater treated. Compared with the liquid phase + solid phase sintering process, the preparation method has the advantages of less wastewater treatment volume, no need for spray drying process, and lower energy consumption; (2) the present invention uses a fluorine replenisher, which replenishes the F loss and ensures the component completion and phase purity; (3) the fluorine replenisher used in the preparation method also acts as a binder, and the fiberization of the binder is achieved through high-speed shear force, so that different particles in the raw material after ball milling are bonded; the sodium vanadium fluorophosphate precursor obtained after the bonding body raw material is rolled and granulated by a roller granulator has higher density and better uniformity, so the unit volume loading is higher in large-scale production, which is conducive to improving production capacity; (4) the preparation method obtains the carbon-coated sodium vanadium fluorophosphate positive electrode material after one-time sintering, which improves the conductivity of the positive electrode material; (5) the prepared carbon-coated sodium vanadium fluorophosphate positive electrode material has a higher powder compaction density; (6) the carbon-coated sodium vanadium fluorophosphate positive electrode material obtained by the preparation method has a higher specific capacity;
[0086] It is worth noting that in the preparation method of the present application, the sodium vanadium fluorophosphate raw material, the carbon source and the fluorine replenishing agent are pre-dispersed and mixed to obtain a pre-mixed raw material, wherein the carbon source is glucose or citric acid, and the mass of the carbon source is 1-10wt% of the total mass of the sodium vanadium fluorophosphate raw material; the fluorine replenishing agent is polyvinylidene fluoride or polytetrafluoroethylene, and the mass of the fluorine replenishing agent is 1-8wt% of the total mass of the sodium vanadium fluorophosphate raw material; the pre-mixed raw material is ball-milled, and the median particle size D50 of the raw material particles after ball milling is ≤6 microns; the fluorine replenishing agent used is also used as a binder, and is passed through a high-speed The disperser disperses the raw materials after ball milling by high-speed shearing. The speed of the high-speed disperser is set to 800-1800rpm. The fiberization of the adhesive is achieved through high-speed shearing force, and different particles in the raw materials after ball milling are bonded. The bonding body raw materials are roller-pressed and granulated by a roller granulator. The obtained sodium vanadium fluorophosphate precursor has higher density, so the unit volume loading is higher in large-scale production, which is conducive to increasing production capacity. The carbon-coated sodium vanadium fluorophosphate positive electrode material is obtained after one-time sintering, which has good conductivity and high specific capacity, and can be continuously produced on a large scale.
[0087] The method for preparing the positive electrode material provided by the present invention uses low-cost carbon sources such as glucose or citric acid as raw materials, thereby reducing the production cost of the positive electrode material.
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a positive electrode material, characterized in that: The preparation method comprises the following steps: Step 1, putting the sodium vanadium fluorophosphate raw material, the carbon source and the fluorine replenishing agent into a high-speed disperser for pre-dispersion and mixing to obtain a pre-mixed raw material; Step 2, grinding the premixed raw materials by a ball mill; Step 3, sending the ball-milled raw materials into a high-speed disperser for high-speed shearing and dispersion until a bonding raw material is formed; Step 4, rolling and granulating the bonded body raw material through a roller granulator to obtain a sodium vanadium fluorophosphate precursor; Step 5: sinter the sodium vanadium fluorophosphate precursor once to obtain a carbon-coated sodium vanadium fluorophosphate positive electrode material.
2. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 1, the sodium vanadium fluorophosphate raw material includes a sodium source / fluorine source, a phosphorus source and a vanadium source; The sodium source / fluorine source is sodium fluoride, the phosphorus source is ammonium dihydrogen phosphate or phosphoric acid, and the vanadium source is vanadium pentoxide or ammonium metavanadate; wherein the molar ratio of the sodium source / fluorine source, the phosphorus source and the vanadium source is 3:2:2; The carbon source is glucose or citric acid, and the mass of the carbon source is 1-10wt% of the total mass of the sodium vanadium fluorophosphate raw material; The fluorine replenisher is used to replenish fluorine loss to ensure the completion and phase purity of the synthesized sodium vanadium fluorophosphate components; the fluorine replenisher also acts as a binder to bond the particles during high-speed shear dispersion, and after roller granulation, the sodium vanadium fluorophosphate precursor has a higher density; wherein the fluorine replenisher is polyvinylidene fluoride or polytetrafluoroethylene, and the mass of the fluorine replenisher is 1-8wt% of the total mass of the sodium vanadium fluorophosphate raw material.
3. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 2, the median particle size D50 of the raw material particles after ball milling is ≤6 microns.
4. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 3, when the high-speed disperser performs high-speed shear dispersion, the rotation speed of the high-speed disperser is 800-1800 rpm.
5. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 4, the roller granulator performs roller granulation with a roller pressure of ≥7 MPa.
6. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 5, the primary sintering is a step-by-step sintering, specifically: After the sodium vanadium fluorophosphate precursor is subjected to a first sintering reaction at a first sintering temperature, the temperature is raised to a second sintering temperature for a second sintering reaction; Wherein, the conditions of the first sintering reaction are: The first sintering temperature is 300-400°C, and the first sintering reaction time is 5-10h; The conditions of the second sintering reaction are: The second sintering temperature is 500-750°C, and the second sintering reaction time is 8-12h.
7. A pole piece, characterized in that: The invention comprises a carbon-coated sodium vanadium fluorophosphate positive electrode material prepared by the preparation method according to any one of claims 1 to 6.
8. A battery, characterized in that: It comprises the carbon-coated sodium vanadium fluorophosphate positive electrode material prepared by the preparation method according to any one of claims 1 to 6 or the electrode sheet according to claim 7.
Citation Information
Patent Citations
High-compaction single-crystal lithium vanadium fluorophosphate positive electrode material as well as preparation method and application thereof
CN114351252A
Battery dry-method pole piece, preparation method thereof and battery
CN117096261A
Carbon-coated sodium vanadium fluorophosphate positive electrode material and preparation method thereof, positive electrode plate and secondary battery
CN119008903A
Positive electrode material and preparation method thereof, positive electrode plate and sodium ion battery
CN119324218A
Method for preparing carbon-coated sodium iron fluorophosphate from waste lithium iron phosphate, and use thereof
WO2024125561A1